Effects of 1-month R-α-lipoic acid supplementation on humans oxidative status: a pilot study - Vigna, Luisella; Solimena, Giuseppe; Bamonti, Fabrizia; Arcaro, Marina; Fenoglio, Chiara; Oldoni, Emanuela; Dellanoce, Cinzia; Rossi, Paola; Gori, Francesca; Figliola, Rocco; Cighetti, Giuliana (Progress in Nutrition, 2017)
Alpha-lipoic acid (α-LA), an endogenous antioxidant co-factor of important enzymatic complexes, is rapidly catabolised in dihydrolipoic acid becoming an even stronger antioxidant for strengthening the activity of endogenous antioxidants (vitamin C, E, glutathione). AIM. To evaluate the effects of an oral use liquid formulation containing the natural and more active α-lipoic acid (R-αLA) enantiomer on 20 subjects oxidative status: 10 apparently healthy subjects and 10 affected by risk factors (such as excess weight, hypertension) and/or diseases (such as diabetes, polyneuropathy). The subjects’ oxidative status was assessed by measuring blood concentrations of: reactive oxygen species (ROS), total antioxidant capacity (TAC), glutathione, Vitamin C and Vitamin E at baseline (T0) and after 1-month’ supplementation (T1) with R-αLA. Moreover, cysteine and homocysteine levels, well-known cardiovascular risk factors, were measured. Results. Interesting findings on the cellular antioxidant regeneration cycle: a significant decrease in reduced glutathione (GSH) levels and GSH/GSSG ratio, a slight downward trend in oxidised glutathione (GSSG) and vitamin C and E concentrations. Due to the brief treatment period, the study did not however show any significant differences in the oxidative “status” balancing parameters (ROS and TAC) and on homocysteine and cysteine levels. Remarkable were the findings regarding patients who reported a lessening, or even the disappearance, of pain symptoms. Comment. After 1-month’ treatment, the R-αLA oral use liquid formulation seemed to reinforce endogenous antioxidant activity and, notably, helped mitigate the pain symptoms typical of several stress oxidative-dependent diseases. This effect could probably depend on greater bioavailability of the liquid formulation.